Resistance of potato genotypes to late blight. - OXLEY, H. N. (2023)
Late blight (Phytophthora infestans) is a serious problem in potato crops in southern Brazil due to favorable climatic conditions for the development of the pathogen and the lack of resistant cultivars available in the market. Thus, this study aimed to evaluate the reaction of eight cultivars (Asterix, Catucha, BRS Clara, BRS F63 - Camila, Cristal, BRS F183 - Potira, Markies, and BRS Pérola) and five advanced clones (F05-11-03, F21-07-09, Odone 80-02, F50-08-01, and F63-10-07) to late bight under field conditions. The Agata and the clone CIP392.617-54 were used as susceptible and resistant controls, respectively. The experiments were conducted in the municipality of Pelotas, RS, in the autumn season of 2018 and 2019. Sixty days after planting, the plants were inoculated with the pathogen; and, after one week, the genotypes were evaluated for disease severity and the area under the disease progress curve. ‘Catucha’ was classified as resistant to moderately resistant to P. infestans; ‘Cristal,’ F50-08-01 and ‘BRS Perola’, moderately susceptible to resistant; and ‘BRS F63’ - Camila, F63-10-07, F05-11-03, Asterix, F21-07-09, BRS F183 – Potira, and Odone 80-02, moderately susceptible to susceptible. BRS Clara and Markies showed the greatest variations in both experiments, showing to be susceptible in the autumn of 2018 experiment and moderately resistant in the autumn of 2019 experiment.